2015
DOI: 10.1016/j.bpj.2015.03.021
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Study of Ovalbumin Fibril Formation: The Importance of Fragmentation and End-Joining

Abstract: The ability to control the morphologies of biomolecular aggregates is a central objective in the study of self-assembly processes. The development of predictive models offers the surest route for gaining such control. Under the right conditions, proteins will self-assemble into fibers that may rearrange themselves even further to form diverse structures, including the formation of closed loops. In this study, chicken egg white ovalbumin is used as a model for the study of fibril loops. By monitoring the kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 49 publications
(65 reference statements)
2
21
0
Order By: Relevance
“…They laterally associate and align prior to twisting into mature AFs (Adamcik & Mezzenga, ). In some cases, the growth of protofibrils ends when loops are formed (Kalapothakis et al., ). The amino acid sequences that are frequently involved in fibrillation and actually promote the formation of β‐sheet structures are called core or amylogenic regions (Jansens, Rombouts, et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…They laterally associate and align prior to twisting into mature AFs (Adamcik & Mezzenga, ). In some cases, the growth of protofibrils ends when loops are formed (Kalapothakis et al., ). The amino acid sequences that are frequently involved in fibrillation and actually promote the formation of β‐sheet structures are called core or amylogenic regions (Jansens, Rombouts, et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The initial growth phase was followed by (i) a second growth phase in which the ThT fluorescence still increased, but more slowly than in the initial growth phase and (ii) by a subsequent plateau phase with constant ThT fluorescence. A model for fibril formation that includes seeded linear growth, end‐joining, and fibril fragmentation shows that especially end‐joining (hence the formation of loops) impacts the growth of fibrils at neutral pH (Kalapothakis et al., ). Oxidation of SH groups has little—if any—impact on fibril formation as evidenced by ThT fluorescence (Jansens et al., ).…”
Section: Hen Egg Proteinsmentioning
confidence: 99%
“…Finally, the protofibrils self‐assemble into much longer and stiffer mature fibrils (Hill et al., ). However, it is not always clear whether the same mechanism is involved when amyloid‐like aggregates are formed under other conditions (Kalapothakis et al., ).…”
Section: Amyloid Formation Of Food Proteinsmentioning
confidence: 99%
“…Sonication of preformed hen lysozyme fibrils into small particles and mixing a fraction thereof into a solution of fresh intact hen lysozyme allow immediate formation of second‐generation AFs under conditions which, without seeding, only result in AF after a lag phase of 11 days (pH 2.2 at 57 °C; Sasaki et al., ). Temperature‐dependent seeding has been reported for fibril formation of disulfide‐reduced ovalbumin at 50 °C and neutral pH even though also without seeding there was no apparent lag phase (Kalapothakis et al., ). Hamada and Dobson () showed that preformed β‐lactoglobulin fibrils eliminate the lag phase for fibril formation of disulfide‐reduced β‐lactoglobulin in 3.0 to 5.0 mol/L urea at 37 °C and pH 7.0.…”
Section: Seeding and Cross‐seeding Approaches To Tailor (Food) Protein mentioning
confidence: 99%